Investigation of the driving voltage on the high performance flexible ATF-ECDs based on PET/ITO/NiOX/LiTaO3/WO3/ITO - Jinhong Ye; Mingtao Chen; Hanyu Lu; Hongbing Zhu; Meixiu Wan; Kai Shen; Yaohua Mai (Heliyon, 2024)
High performance flexible all-thin-film electrochromic devices (ATF-ECDs) have been fabricated and systematically investigated by operating with different driving voltages during the electrochromic processes. The device structure (cross-section) and material properties of some main functional layers were presented and analysed. The electrochromic properties including kinetic and spectral tests were systematically investigated through combining chronoamperometry, cyclic voltammetry measurements and optical measurements. In addition, the open circuit memory measurement was also carried out. A much higher driving voltage might lead to a current leakage inside the device during coloring process. A proper driving voltage is needed for achieving high device performances. More details were widely described and deeply discussed.